MSME PROFITS BOOST: The Impact of Revitalization Used Fintech, E-Commerce, and Digital Payments - Christine; Wendi Wendi; Shella Pratamawati; Nizwan Zukhri (Al-Makki Publisher, 2023)
This study aims to examine the influence between financial technology, electronic commerce, and digital payment variables on profit growth variables in MSMEs in Pangkalpinang City, Bangka Belitung Islands Province. The method that the researchers used in this study is an associative method with a quantitative approach that uses primary data sources obtained through the distribution of questionnaires. The sampling method is Nonprobability Sampling with purposive sampling techniques which obtained 100 respondents who are MSME actors. This type of research is quantitative research that is associative. Data analysis techniques use the help of Statistical Package for the Social Sciences (SPSS) software version 25. The results revealed that simultaneously fintech (X1), e-commerce (X2) and digital payment (X3) had a positive and significant effect on profit growth in MSMEs in Pangkalpinang City, while partially fintech variables had a positive and significant effect on profit growth, while e-commerce and digital payment variables did not have a positive and significant effect on profit growth in MSMEs in Pangkalpinang City. The R Square value is 0.504 or 50.4%, so it is concluded that 50.4% of the variation in the dependent variable can be explained by the independent variable. Then the Adjusted R Square value is 0.488 or 48.8%. So it can be concluded that fintech, e-commerce, and digital payments can affect profit growth by 48.8% while the remaining 51.2% is influenced by other variables that were not studied in this study.